2021
DOI: 10.1073/pnas.2106480118
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction of the effect of amino acid changes on the binding affinity between SARS-CoV-2 spike RBD and human ACE2

Abstract: The association of the receptor binding domain (RBD) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein with human angiotensin-converting enzyme 2 (hACE2) represents the first required step for cellular entry. SARS-CoV-2 has continued to evolve with the emergence of several novel variants, and amino acid changes in the RBD have been implicated with increased fitness and potential for immune evasion. Reliably predicting the effect of amino acid changes on the ability of the RBD to int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 109 publications
5
63
0
Order By: Relevance
“…These observation are consistent with the hypothesis that the evolution of the virus in the human population can occur not only by escaping immune pressure or increasing the affinity of RBD towards the canonical ACE2 receptor, as commonly assumed [98], but also through adaptation of the virus to alternative receptors and co-receptors of expressed on-host cells. In the retrospective analysis, the discovered cluster of FGFR interacting with SARS-CoV-2 spike amino acids was compared with corresponding amino acids of the These observation are consistent with the hypothesis that the evolution of the virus in the human population can occur not only by escaping immune pressure or increasing the affinity of RBD towards the canonical ACE2 receptor, as commonly assumed [98], but also through adaptation of the virus to alternative receptors and co-receptors of expressed on-host cells. In the retrospective analysis, the discovered cluster of FGFR interacting with SARS-CoV-2 spike amino acids was compared with corresponding amino acids of the SARS-CoV spike.…”
Section: Primary Structure Analysis Of Receptor-binding Aa Clusters O...supporting
confidence: 91%
See 1 more Smart Citation
“…These observation are consistent with the hypothesis that the evolution of the virus in the human population can occur not only by escaping immune pressure or increasing the affinity of RBD towards the canonical ACE2 receptor, as commonly assumed [98], but also through adaptation of the virus to alternative receptors and co-receptors of expressed on-host cells. In the retrospective analysis, the discovered cluster of FGFR interacting with SARS-CoV-2 spike amino acids was compared with corresponding amino acids of the These observation are consistent with the hypothesis that the evolution of the virus in the human population can occur not only by escaping immune pressure or increasing the affinity of RBD towards the canonical ACE2 receptor, as commonly assumed [98], but also through adaptation of the virus to alternative receptors and co-receptors of expressed on-host cells. In the retrospective analysis, the discovered cluster of FGFR interacting with SARS-CoV-2 spike amino acids was compared with corresponding amino acids of the SARS-CoV spike.…”
Section: Primary Structure Analysis Of Receptor-binding Aa Clusters O...supporting
confidence: 91%
“…Calu-3 cells are sensitive to SARS-CoV-2 infection and, like other human cancer cells, are commonly used for propagation of the SARS-CoV and SARS-CoV-2 viruses in cell culture [30,72,77,[114][115][116][117]. These observation are consistent with the hypothesis that the evolution of the virus in the human population can occur not only by escaping immune pressure and increasing the affinity of RBD to ACE2, as commonly assumed [98], but also through exchanging virus receptors and co-receptors during the adaptation to a new host cell [1,10].…”
Section: Development Of Phage-derived Probes For Monitoring Virus Evo...supporting
confidence: 83%
“…Close to them within the RBD, K417N, and K417T mutations have been repeatedly described to protect against binding to certain monoclonal antibodies [55]. Nevertheless, both K417N and K417T are expected to moderately decrease ACE2-binding affinity [76,147,148]. The main impact of the K417N mutation seems to be its ability to destabilize the RBD-down conformation (Figure 1B), thereby increasing the propensity of the open configuration [36].…”
Section: Other Rbd Mutationsmentioning
confidence: 93%
“…For instance, we have shown that one of the aromatic rings of TPE core forms a cation–π interaction with –NH group of Asn501. However, some of the recent SARS-CoV-2 variants have Tyr in place of Asn at this position ( Chen et al, 2021 ; Dejnirattisai et al, 2021 ). Such mutations may affect the quality of TPE binding to the spike protein, which may or may not affect the emission patterns.…”
Section: Discussionmentioning
confidence: 99%